Usaha Indekost di Sekitar Kawasan Universitas Batanghari Jambi 1985-2012 - Ramadhani, Laela (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2020)
AbstractThe problem in this study is how the development of boarding businesses in 1985-2012 and the socio-economic life of the Sungai Putri village community. The purpose of this study refers to the issues raised, the aim is to explain the development of boarding businesses around the area of Batanghari University Jambi from 1985-2012 and describe the impact of the economic life of the communities around Sungai Putri. The boarding house business is developing in several sectors such as infrastructure, education, and entrepreneurship. The economic life of the Sungai Putri village community is as diverse as traders, entrepreneurs, and other occupations. The conclusion of this research is that the boarding house business has experienced significant developments in several sectors that support the development of the community around the Sungai Putri village. It can be said that this is prosperous as seen from the economic activities in the communities around the Sungai Putri village.Keywords: Boarding house, establishment factor, development.AbstrakPermasalahan dalam penelitian ini bagaimana perkembangan usaha indekost pada Tahun 1985-2012 dan kehidupan sosial ekonomi masyarakat kelurahan Sungai Putri. Tujuan dari penelitian ini mengacu pada permasalahan yang diangkat, maka tujuannya menjelaskan perkembangan usaha indekos disekitar kawasan Universitas Batanghari Jambi dari Tahun 1985-2012 dan mendeskripsikan dampak kehidupan ekonomi masyarakat sekitar kelurahan Sungai Putri. Usaha indekost mengalami perkembangan di beberapa sektor seperti infrastruktur, pendidikan, dan wirausaha. Kehidupan ekonomi masyarakat kelurahan Sungai Putri sudah beranekaragam seperti pedagang, wiraswasta, dan pekerjaan lainnya. Kesimpulan dari penelitian ini yaitu usaha indekost mengalami perkembangan yang signifikan di beberapa sektor yang menunjang perkembangan masyarakat di sekitar kelurahana Sungai Putri dapat dikatakan sejahtera hal ini dilihat dari kegiatan ekonomi yang terdapat di masyarakat sekitar kelurahan Sungai Putri.Kata Kunci : Indekost, Faktor Berdirinya, Perkembangan.